Communities of Resistance: African Canadians and African Americans in Antebellum Toronto - Smardz Frost, Karolyn (Ontario History, 2007)
Before the Civil War, what is now Ontario was the main destination of passengers on the fabled “Underground Railroad.” Relatively little scholarly attention has been paid to the Black community that grew up in the province’s largest city. Nearly two percent of Toronto’s population was made up of African American immigrants by the mid-nineteenth century. These newcomers joined in efforts mounted by the existing African Canadian population to resist both slavery in the United States and racial discrimination on both sides of the US-Canadian border. This paper examines three intertwined strands of Black resistance in Toronto: political protest and overt anti-slavery; what the author calls “practical abolitionism,” largely consisting of fugitive slave reception and assistance; and anti-racism, coupled with what would come to be termed “racial uplift.”